The Influence of Social Media Marketing and Live Streaming on Skintific Product Purchases via TikTok in Jambi City - Nita Safitri; Musnaini Musnaini; Sigit Indrawijaya (Jurnal Bintang Manajemen, 2025)
This research aimed to examine the influence of social media marketing and live streaming on purchasing decisions for skintific products through the TikTok platform in Jambi City. This research is a type of quantitative research. Determination of the number of samples in this research was 96 respondents with the sampling technique used as Purposive Sampling and the sampling method used was Non-Probability Sampling. The primary data used was obtained through a digital questionnaire, namely Google Form with a Likert scale. The data analysis method in this research uses SPSS (Statistical Product and Service Solution) using IBM SPSS Statistics 25 For Windows software. The results of this research indicate that social media marketing and live streaming have a positive and significant effect on purchasing decisions for skintific products through the TikTok platform in Jambi City.